Financial Management Accountability of Subak Local Institutions in A Balanced Values of Hinduism and Multi-Strategic Role - Purnamawati, I Gusti Ayu; Rahayu, Sri (International Journal of Organizational Behavior and Policy, 2025)
This research aims to reveal local Subak institutions' financial management accountability in a balanced and multi-strategic role. This research was conducted using qualitative methods to understand the phenomena experienced by research subjects. Data was collected from primary sources, namely data obtained directly from informants and secondary sources. This research was conducted at Subak Kali Kembar, Jembrana Regency, Bali. Interviews were conducted with Kelihan and Subak members. The results of this research show that the source of funds for Kali Kembar subak in carrying out operational activities is obtained from subak krama (contributions) and aid funds from the government; Subak's financial management process through internal and external funds, financial management accountability is carried out; The difference in financial management lies in the form of the accountability report; To establish accountability in the financial management provided, all Kramas uphold the concepts and values of Hinduism and foster mutual trust between Subak Kramas. Prajuru's understanding of bookkeeping still needs to be improved. Therefore, Subak administrators always try to present good accountability, even though they do not refer to accounting standards. The financial management of the Subak organization does not overlap between krama and Subak administrators and the use of finances in the form of Subak financial cash reports should be presented openly at meetings.